Relationship Between Educational Level and Attitudes Towards Alcohol Conversations in Healthcare: A Cross-Sectional Survey Conducted in Four European Countries - Nadine Karlsson; Janna Skagerström; Janna Skagerström; Amy O'Donnell; Latifa Abidi; Kristin Thomas; Per Nilsen; Torgeir Gilje Lid; Torgeir Gilje Lid (International Journal of Public Health, 2023)
Objectives: To examine the association between educational level and attitudes towards alcohol conversations in healthcare using population-based surveys of adults in England, the Netherlands, Norway, and Sweden; and to compare attitudes towards alcohol conversations in healthcare between these four countries.Methods: Cross-sectional surveys were conducted amongst adults in the general population in England (n = 3,499), the Netherlands (n = 2,173), Norway (n = 1,208), and Sweden (n = 3,000). Logistic regression analysis was used to examine associations between attitudes towards alcohol conversations in healthcare and educational level, key demographic variables, alcohol consumption, and country of residence.Results: In all four countries, low educational level (p < 0.001) and male gender (p < 0.001) were associated with holding negative attitudes towards discussing alcohol in healthcare. Risky drinkers had more negative attitudes than low risky drinkers towards discussing alcohol in healthcare (p < 0.001) in all countries except England (p = 0.48), and also reported low levels of perceived honesty and confidence in healthcare (p < 0.001).Conclusion: These findings highlight the importance of considering patients’ socio-economic status when developing and implementing alcohol prevention interventions in healthcare.